Strategi Reward dan Punishment dalam Meningkatkan Motivasi dan Kinerja Agen di PT Asuransi Jiwa Sequis Life Cabang Medan - Nurul Afida; Zainarti Zainarti (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This article aims to analyze the strategies of reward and punishment in enhancing the motivation and performance of agents at PT Asuransi Jiwa Sequis Life Medan Branch. This study employs a quantitative approach with a survey method. Data were collected through questionnaires distributed to 50 insurance agents working at the Medan branch. Data analysis was conducted using descriptive and inferential statistics. The findings indicate that the reward strategies implemented by the company, such as recognition and bonuses, positively impact the improvement of agents' motivation and performance. On the other hand, the application of punishment strategies, such as sanctions or incentive reductions, has also proven effective in improving discipline and performance. Overall, the combination of reward and punishment strategies significantly enhances the motivation and performance of agents at PT Asuransi Jiwa Sequis Life Medan Branch.